(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
In 1945, Wolfgang Hahn introduced his difference operator D_q,ω, which is defined by where ω_0=ω1-q with 0<q<1, ω>0. In this paper, we establish Leibniz’s rule and Fubini’s theorem associated with this Hahn difference operator.